Comparative description of motive preparedness of schoolchildren is 8—9 classes - Іващенко, О. В.; Макарова, О. А. (Physical Education Theory and Methodology, 2013)
Aim of work — to define 8—9 classes to the feature of motive preparedness of schoolchildren. For the decision of the put tasks the next methods of research: were used theoretical analysis and generalization of scientific and methodical literature, pedagogical supervisions, testing, methods of mathematical statistics. Conclusions. Level of functional preparedness of schoolchildren 8—9 classes are estimated as middle. Mean values of testing results can be reference-points for self-perfection of motive preparedness of schoolchildren of eighth and ninth classes. Research results testify that under act of engaging in physical exercises the indexes of static and speed force became better in the students of middle classes. The system of motive preparation will be effective only then, when an educational process will be built on the basis of conformities to law of development of organism and correctly neat facilities and methods of educating.